2013
DOI: 10.1080/1461670x.2013.831228
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Tango

Abstract: The relationship between politicians and journalists is often portrayed as an intimate dance, characterized by intFerdependence. The political agenda-setting approach has been used successfully to improve our knowledge of certain aspects of this power relationship. This study builds on this line of research, but in more depth by conducting a detailed and reciprocal analysis of the relationship between press coverage and parliamentary questions in the Netherlands (1995Á2010). Our macro-level approach shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…By focusing on the share of questions to each minister, we exclude variation in the number of questions asked to each minister, which is not the focus of our analysis. Previous analyses have shown that media attention has a large impact on the topics covered in parliamentary questions (Van Aelst and Vliegenthart 2014;. The second way to measure our dependent variable effectively controls for this.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By focusing on the share of questions to each minister, we exclude variation in the number of questions asked to each minister, which is not the focus of our analysis. Previous analyses have shown that media attention has a large impact on the topics covered in parliamentary questions (Van Aelst and Vliegenthart 2014;. The second way to measure our dependent variable effectively controls for this.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature on parliamentary questions two approaches have been prominent: the first focuses on the use of parliamentary questions as an electoral tool for individual MPs (Bailer 2011;Mayhew 1974;Russo and Wiberg 2010;Saalfeld 2011). The second examines the relationship between the media agenda and the parliamentary agenda as reflected by parliamentary questions (Van Aelst and Vliegenthart 2014;Vliegenthart 2010, 2012). Despite the fact that we know that MP behaviour reflects the aims and strategies of their parties, most of this work aims to explain how many questions individual MPs ask or the topics they focus on.…”
mentioning
confidence: 99%
“…Therefore, a journalistic heuristic to focus on messages by favored political actors would to some extent be insufficient, as even the most favored actors send more messages than a media outlet could report on. Thus, editors and journalists need to ignore most messages, even those from political actors they prefer the most (e.g., Meyer, Haselmayer, & Wagner, 2015;Van Aelst & Vliegenthart, 2014;Van Santen et al, 2015). 1 When choosing among messages from the same political actor, journalists and editors will therefore prefer to report on campaign messages that have the additional benefit of containing (higher) news value.…”
Section: News Value As a Moderator Of The Partisan Bias Effectmentioning
confidence: 99%
“…Previous research has considered party issue agenda-setting in the media (Brandenburg, 2002(Brandenburg, , 2006Hopmann et al, 2012) or the visibility of political actors in the news (Cook, 1988;Gattermann & Vasilopoulou, 2015;Kriesi, 2012;Tresch, 2009). More recent studies have focused on media gatekeeping of individual messages such as parliamentary questions (Van Aelst & Vliegenthart, 2014;Van Santen et al, 2015) and party pledges (Kostadinova, 2015). So far, little research on gatekeeping has looked at press releases, with a few exceptions from the United States (Flowers, Haynes, & Crespin, 2003;Grimmer, 2010Grimmer, , 2013 and Europe (Helfer & Van Aelst, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the media on the parliamentary agenda in the Netherlands has grown considerably over time (Van Noije, Kleinnijenhuis, & Oegema, 2008). Dutch parliamentary questions are, indeed, almost always inspired or influenced by media attention (Van Aelst & Vliegenthart, 2013). Figure 10.1 shows the number of written questions asked by Dutch members of parliament about tobacco control.…”
Section: Media Advocacymentioning
confidence: 99%